Procyanidin B2 from lotus seedpod regulate NO/ADMA/DDAH pathway to treat insomnia in rats. (16th April 2019) - Xiao, Hong‐Bo; Wang, Yi‐Shan; Liang, Lin; Lu, XiangYang; Sun, Zhi‐Liang
Abstract: Recent studies show that nitric oxide/asymmetric dimethylarginine/dimethylarginine dimethylaminohydrolase (NO/ADMA/DDAH) pathway may contribute to the development of sleep disorder. The objective of this study was to explore the inhibitory effect of procyanidin B2 from lotus seedpod (LSPC), a naturally occurring catechin compound, on insomnia and the mechanisms involved. The experiments were performed in brain from Sprague‐Dawley rat control and insomniac rats treated or not with LSPC (15, 30, and 45 mg/kg, intragastrically) for 7 days. LSPC treatment reduced walking time and forelimb lifting‐up frequency, cerebral levels of noradrenaline, glutamic acid, ADMA, sleep latency, and 8‐isoprostane; increased sleep duration, cerebral concentrations of 5‐hydroxytryptamine, γ‐aminobutyric acid, and NO concomitantly with upregulated cerebral expression of DDAH 1, DDAH2, and neuronal NO synthases in insomniac rats. The present results suggest that LSPC may regulate NO/ADMA/DDAH pathway by inhibiting oxidative stress to treat insomnia in rats when sleep evaluation was achieved on the basis of behavioral criteria.